The effect of constant light on oxidative status of rat brain, liver, and kidney - Baydas, G; Ercel, E; Dönder, E; Türkoglu, A; Canpolat, L; Akyol, A (Blackwell Science Ltd, 1998)
[Abstract Not Available]